Modelling trades-through in a limited order book using Hawkes processes - Ioane Muni Toke; Fabrizio Pomponio (Kiel Institute for the World Economy (IfW), 2011)
We model trades-through, i.e. transactions that reach at least the second level of limit orders in an order book. Using tick-by-tick data on Euronext-traded stocks, we show that a simple bivariate Hawkes process fits nicely our empirical observations of trades-through. We show that the cross-influence of bid and ask trades-through is weak.
Keywords: C32; C51; G14; 330; Hawkes processes; limit order book; trades-through; highfrequency trading; microstructure; Börsenkurs; Bid-Ask Spread; Wertpapierhandel; Mikrostrukturanalyse; Stochastischer Prozess; Theorie; EU-Staaten